Seeking asylum in Australia: immigration detention, human rights and mental health care. (August 2013) - Newman, Louise; Proctor, Nicholas; Dudley, Michael
Objective: The article aims to discuss the impact of mandatory detention and human rights violations on the mental health of asylum seekers and the implications for psychiatrists and health professionals. Conclusions: Advocacy for human rights and engagement in social debate are core ethical and professional responsibilities. Clinicians need to maintain a focus on ethical obligations.